Integrated Lean AHP and Taguchi for Supplier Quality Decisions: Pendekatan Terpadu Lean AHP dan Taguchi untuk Pengambilan Keputusan Kualitas Pemasok - Arifianto , Rahmat; Sulistiyowati, Wiwik (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Quality control and supplier selection are critical components in manufacturing systems to ensure process stability and cost efficiency. Specific Background: Companies in the food and small-scale production sector frequently encounter non-value-added activities and variability in raw material quality that affect operational performance. Knowledge Gap: Previous studies have discussed lean thinking, Analytical Hierarchy Process, and Taguchi Loss Function separately, yet limited research integrates these approaches within a single decision-making framework for supplier evaluation and quality control. Aims: This study aims to analyze production inefficiencies and determine optimal supplier selection criteria using an integrated Lean Thinking, AHP, and Taguchi Loss Function approach. Results: The findings identify dominant waste categories, prioritize supplier evaluation criteria, and quantify quality loss to support structured decision making. Novelty: The study presents a combined methodological framework that links waste identification, multi-criteria decision analysis, and quality loss measurement within one operational model. Implications: The proposed framework provides a systematic basis for managerial decision making in improving production consistency, minimizing quality deviation, and strengthening supplier performance evaluation in manufacturing systems. Keywords: Lean Thinking, Supplier Evaluation, Analytical Hierarchy Process, Taguchi Loss Function, Quality Control Key Findings Highlights Waste categories were systematically identified within the production workflow. Multi-criteria prioritization structured supplier ranking decisions. Quality deviation was quantified using a loss-based measurement model.